Local Actions Prevent Land Conversion through Tourism in Rokan Koto Ruang Village, Rokan Hulu, Riau, Indonesia - El Amady M. Rawa; Yanti Rina Novia; Alexuxanto; Dinata Marta (E3S Web of Conferences)
This study discusses the environmental aspects of Koto rice field tourism in Rokan Koto Ruang Village. In Rokan Koto Ruang Village, there are already three well-known natural and historical tourist attractions. However, the village government has established rice field tourism that relies on selfie bridges. On the other hand, there has been a conversion of agricultural land and rubber plantations into oil palm plantations by up to 90%, with oil palm plantations even found on the edges and in the middle of rice fields. This research is qualitative with a phenomenological approach, using in-depth interviews, observations, and focus group discussions (FGDs). The data was analyzed using a domain approach to identify the most prominent domains connected to the research standpoint. The findings indicate that the development of Koto rice field tourism aims to conserve rice fields in Rokan Koto Ruang Village. The novelty of this research is that it positions tourism as a policy option for conservation. This research significantly contributes to environmental science, particularly in utilizing non-environmental services for environmental conservation.